The Effect of the use of Silica Sand Before and After Physical Activation on Acceleration of 4-Step Gasoline Motorcycle Engine - Akhmad Riszal; Sandy Dwi Hardin; Herry Wardono; M. Dyan Susila ES; A. Yudi Eka Risano (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2022)
This research was conducted with the aim of knowing the Effect of using silica sand before and after physical activation on the acceleration of a 4-stroke gasoline motorcycle engine. This research was conducted by testing the acceleration 0 – 80 km/hour and 40 – 80 km/hour with variations in the composition of tapioca in the pellet mixture (1%, 2%, and 3%) and variations in temperature activation (150?C, 200?). C, and 250?C). The silica sand pellets used in this study were 10 mm in diameter with a thickness of 3 mm, which had been activated for 60 minutes. The results showed that the use of silica sand had an effect on the acceleration of a 4-stroke gasoline motorcycle. The best composition of silica sand pellets occurs in the amount of tapioca 3% and with an activation temperature of 250?C, which can increase the acceleration by 12.45% at an acceleration of 0 – 80 km/hour.